Gaston Vidal: “Two Acts in Front of a Conscience,” “Shakespearean Story” (The Sources of I. Babel’s Stories about the First World War) - Elena I. Pogorelskaia (Литературный факт, 2023)
For the first time, the 11th and 15th chapters of G. Vidal’s book “Characters and Anecdotes of the Great War” (Paris, 1918) were translated into Russian. These chapters served as the source for the plot of three stories by I. Babel (1920) about the First World War — “On the Field of Honor,” “Deserter,” “The Family of Father Maresco.” The publication of the translation is accompanied by an analytical article in which the stories that became the first experience of military prose for the future author of “Red Cavalry” are compared with Vidal’s texts. Babel’s stories “On the Field of Honor” and “The Deserter” were written based on the 11th chapter of Vidal, and the 15th chapter was rewrote by him into the story “The Family of Father Maresco.” Babel preserved the storylines, details of front-line life described by Vidal, individual replicas coincide almost verbatim, but the form of presentation in them differs from the French original. Vidal’s narration is in the first person, while Babel’s in the first two stories is from the third person. Detailed psychological characteristics of the characters and detailed descriptions of the situation from Vidal’s book by Babel are given more concise and succinctly. His stories cannot be considered as a translation in its purest form, rather one can talk about an arrangement or even an interpretation of a French source. At the same time, both Vidal and Babel clearly show the brutality of war and victims caused by the war.